My Southern Home : the South and Its People. - Brown, William Wells (The University of North Carolina Press, 2011)
A prolific and celebrated writer who worked within several genres, William Wells Brown (1814-84) is now firmly established in the American canon, often recognized as the first African American novelist for his Clotel (1853). Born enslaved in Kentucky, Brown escaped to Ohio in 1834. After his escape, he was involved with the Underground Railroad, spent several years in Europe evading recapture under the Fugitive Slave Act, and finally returned to the United States after his freedom was purchased in 1854. In Boston, he continued his work as an outspoken abolitionist, memoirist, novelist, journal.